International bibliography of the social sciences 1968 - SilverPlatter Information, Inc.; British Library of Political and Economic Science; Ovid Technologies, Inc. (New York, N.Y. : Ovid Technologies, 1968)
Contains core social sciences and related materials from over 100 countries in more than 90 languages(including over 2600 journals and books, book reviews, and book chapters).
Title from database guide screen (viewed Dec. 3, 2004).
Previously published by SilverPlatter Information <Oct. 19, 1998>.
Also issued on CD-ROM.
Mode of access: World Wide Web.
Compiled by the British Library of Political & Economic Science of the London School of Economics & Political Science.
Keywords: Social sciences -- Bibliography